A Study of Automatic Operation System Principle Module for Open-pit Mine Truck Transportation - LU Xiangyang; TAN Shaojun; LI Xun; XU Biao; HE Haixing; HE Yunxiang; HU Jian (Kongzhi Yu Xinxi Jishu)
Referring to the features of truck transportation in open-pit mine as being of planned, organized and operation zone closed, an automatic operation system principle module is proposed. It is composed of operation planning layer, operation management and supervision layer as well as truck operation layer. By resolving the task of each layer into appropriate function blocks and specifying the function requirement for each block, the principle that how the truck operates automatically according to human desire is expounded, hence the top design outline of the automatic truck operation system is delineated. The proposed automatic operation system has been tested for one year by single truck and has been commissioning for 5 months by fleet in mine sites, showing its technical feasibility and usefulness to the mine operator.